COMPETITIVENESS OF INDONESIAN FISHERY PRODUCTS IN THE GLOBAL MARKET: A LITERATURE REVIEW OF DETERMINANTS AND IMPROVEMENT STRATEGIES - Muhammad Masykur Abdillah; Al-Amin (Adisam Publisher, 2025)
Indonesia is one of the main exporters of fishery products in the global market, supported by its rich marine resources and comparative advantages in several commodities such as tuna, shrimp, and seaweed. However, the competitiveness of Indonesian fishery products still faces challenges in the form of intense competition, fluctuations in demand, and demands for higher quality and sustainability standards from the international market. This study aims to identify the determinants of competitiveness and formulate strategies to improve the competitiveness of Indonesian fishery products through a literature review. The results showed that the implementation of international quality standards, innovation of value-added processed products, logistics and cold chain efficiency, and strengthening the traceability system are the main factors determining competitiveness. In addition, strengthening human resource capacity, access to financing, market diversification, and multi-stakeholder collaboration are effective strategies to strengthen Indonesia's position as a competitive and sustainable fisheries exporter in the global market.